1997
DOI: 10.1074/jbc.272.4.2149
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Recombinant Fusions of Lipopolysaccharide Binding Protein and Bactericidal/Permeability-increasing Protein

Abstract: had greater heparin binding capacities in vitro and were cleared more rapidly from the plasma of whole animals. Taken together, these data better define how closely related proteins such as BPI and LBP can have opposing effects on the body's response to LPS. Bacterial endotoxin or lipopolysaccharide (LPS),1 a major component of the outer membrane of Gram-negative bacteria, is a potent mediator of the inflammatory response. Because Gram-negative sepsis remains one of the primary causes of severe systemic inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 40 publications
3
79
0
Order By: Relevance
“…In contrast to the effect of binding of LBP to endotoxin, binding of BPI does not lead to extraction and transfer of endotoxin to CD14 and thus can preclude MD-2/TLR4-dependent cell activation by endotoxin [51,66]. This difference reflects differences in the structural and functional properties of the C-terminal domain of LBP and of BPI [48,51,81,107]. Additional differences in the structural and functional properties of the N-terminal domain of BPI and of LBP account for the higher affinity of BPI (vs. LBP) for purified or outer membrane-inserted endotoxin [9,52,53].…”
Section: Bpi Actions During Host: Gnb Interactionsmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast to the effect of binding of LBP to endotoxin, binding of BPI does not lead to extraction and transfer of endotoxin to CD14 and thus can preclude MD-2/TLR4-dependent cell activation by endotoxin [51,66]. This difference reflects differences in the structural and functional properties of the C-terminal domain of LBP and of BPI [48,51,81,107]. Additional differences in the structural and functional properties of the N-terminal domain of BPI and of LBP account for the higher affinity of BPI (vs. LBP) for purified or outer membrane-inserted endotoxin [9,52,53].…”
Section: Bpi Actions During Host: Gnb Interactionsmentioning
confidence: 96%
“…Basic residues clustered at the far end of the amino-terminal domain of BPI are thought to mediate initial electrostatic interactions with acidic sites of endotoxin located close to the lipid A region [47]. In addition, apolar pockets were demonstrated on the concave side of the molecule where host-derived phospholipids can be bound [46] that may be needed to stabilize the water soluble folded structure of BPI [46,48]. Studies using the recombinant amino-terminal domain of BPI alone or recombinant human BPI N /LBP C and LBP N /BPI C chimeric fusion proteins [48,49] have confirmed that the N-terminal domain (minimal structure of residues 13-191; [50]) is responsible for the antimicrobial cytotoxicity [45] and endotoxin-neutralizating properties of BPI [9,49] whereas the C-terminal domain of BPI is needed for BPI-dependent delivery of intact GNB and cell-fee endotoxin-rich particles to specific host cells [51][52][53].…”
Section: Bpi: Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, LBP, BPI, and previously described chimeric proteins of LBP and BPI (39) have been utilized with metabolically labeled preparations of Escherichia coli K12 LPS (40) to further define the role of the COOH-terminal domain of BPI and LBP in delivery of endotoxin to specific cellular and extracellular host targets. We compared the effects of these proteins on the binding of LPS to and activation of enriched populations of leukocytes and on the interaction of LPS with sCD14.…”
mentioning
confidence: 99%